Effectiveness of Children's Music Therapy on Changes in Hospitalized Children's Anxiety Levels: Quasi Experimental Study - Finna Rachma Agustin; Irdawati Irdawati (Indonesian Journal of Global Health Research, 2026)
Hospitalization can cause anxiety in children due to unfamiliar environments, the sound of medical devices, and frightening procedures. This condition causes children to feel scared, cry, have trouble sleeping, and refuse medical treatment, thus hindering the healing process. One of the nonpharmacological interventions that can be used to reduce anxiety is music therapy, because music has a relaxing, calming, and fun effect on children. This study aimed to analyze the effectiveness of children's music therapy on changes in anxiety levels during hospitalization.  The research design used a quasi-experimental approach with a one group pretest-posttest approach on 10 children treated in the children's room of Indriati Hospital. The sampling technique used was purposive sampling. The intervention was given for three days with two sessions per day using selected children's music such as Cocomelon, Cicak-cicak di dinding, and Baby Shark. Anxiety levels were measured using the Facial Image Scale (FIS) and analyzed using the Wilcoxon test. The Wilcoxon test showed values of (Z = -6.797; p < 0.001), which means that there was a significant difference between anxiety levels before and after music therapy. The average anxiety score decreased from 4.53 (severe anxiety) to 2.17 (not anxious). Children's music therapy is effective in reducing anxiety levels during hospitalization and can be used as a nonpharmacological intervention in pediatric nursing care.